Pendampingan Pastoral terhadap Masalah Perselingkuhan - Jeane Priscilia Solissa (Program Pascasarjana UKIM, 2022)
Affair is an important issue because it has a serious impact. This article would like to focus on the problem of wives whose husbands had affairs in the GPM Ewiri Klasis Congregation of South Buru. Wives whose husbands cheat on them experience a holistic impact. The research method used is a pastoral circle: problem description, problem analysis, theological reflection, and pastoral action. Based on the research, it was found that the church needs to develop a holistic model of pastoral care. Therefore, the authors use pastoral counseling steps with the ABC method from Switzer. This pastoral mentoring model is one of the relevant mentoring models to be developed by the church specifically in the Ewiri GPM congregation.